Development of Algebra Monopoly Game Media Based on Rolling Questions for Junior High School - Listiany, Listiany; Murtiyasa, Budi (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
To create an interactive learning atmosphere in the classroom, one way is to use game media that is integrated into learning. There have been many efforts to develop monopoly game media in mathematics learning. However, no research has been found that attempts to develop monopoly game media in mathematics using a learning approach that involves students. Therefore, this research aims to describe the development of monopoly game media on rolling question-based algebra material and analyze the validity and practicality of the media. The development model used in this research is the ADDIE model, an acronym for Analysis, Design, Development, Implementation, and Evaluation. The subject of this research was a class of private junior high school students in Surakarta. The data collection technique uses a response questionnaire obtained from expert validators, teachers, and students. The collected data is then analyzed to determine the validity and practicality of the media that has been developed. The results of data analysis provided by media expert validators obtained an average percentage of 97.6%, while data obtained from practitioners showed an average percentage of 85.6%. Based on the results of this research, it was concluded that the algebra monopoly game media based on rolling questions was declared valid and practical for use as a mathematics learning media in junior high school algebra material.